2013
DOI: 10.1063/1.4794155
|View full text |Cite
|
Sign up to set email alerts
|

Quantum confinement of Bi2S3 in glass with magnetic behavior

Abstract: The novel Bi2S3 quantum dots (QDs) glass nanosystems with unique magnetic properties have been investigated. The monodispersed QDs of size in the range of 3 to 15 nm were grown in the glass matrix. The optical study of these nanosystems clearly demonstrated the size quantization effect resulting in a pronounced band gap variation with QD size. The magnetic properties of the pristine glass and the Bi2S3 QD glass nanosystems were investigated by VSM and SQUID magnetometer. The pristine glass did not show any fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…3(a). A rapid increase in the magnetic susceptibility and the obvious separation between ZFC and FC curves below 7.5 K may be ascribed to the long-range FM order of the Ce 4f ions, or the possible small ferromagnetic clusters 30 . With further cooling down, an obvious drop around 2.8 K in both the ZFC and FC data is observed owing to the superconducting screening and Messier effect, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…3(a). A rapid increase in the magnetic susceptibility and the obvious separation between ZFC and FC curves below 7.5 K may be ascribed to the long-range FM order of the Ce 4f ions, or the possible small ferromagnetic clusters 30 . With further cooling down, an obvious drop around 2.8 K in both the ZFC and FC data is observed owing to the superconducting screening and Messier effect, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Contrasts in the MFM images are caused by the incorporation of Mn 2+ ions into the crystalline structure of the Bi 2 S 3 nanocrystals and indicate that the nanocrystals are magnetic. Recent studies have shown that nanosized Bi 2 S 3 semiconductors behave ferromagnetically, 17 whereas the bulklike Bi 2 S 3 behaves diamagnetically. Figure 2a shows a low intensity contrast in the magnetic phase images (right panel), indicating that the Bi 2 S 3 nanocrystals behave magnetically.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Nanoscale magnetism plays an increasingly significant role in new generation magnetic storage devices and microelectronic industries. Especially some novel materials with Curie temperatures ( T c ) well in excess of room temperature and high saturation magnetization (Ms) remain a continuous priority. Diluted magnetic semiconductor (DMS) quantum dots (QDs) , meet the aforementioned needs and have attracted considerable attention owing to their remarkable magneto-optical effect and three-dimensional quantum confinement of electrons and holes in recent years. It opens the prospect of combining information processing and storage functionalities in one material and has potential applications in the emerging field of spin-based electronics or spintronics, , such as miniaturization of electronic devices, high density data storage systems, and magnetic fluids. Nowadays, much effort has been devoted to the exploration of these new DMS nanomaterials to achieve their practical applications, which at the same time provide precise and insightful guidance for designing and synthesizing unique spintronic materials. …”
Section: Introductionmentioning
confidence: 99%